2015
DOI: 10.4103/0019-509x.175581
|View full text |Cite
|
Sign up to set email alerts
|

A population-based screening program for early detection of common cancers among women in India – methodology and interim results

Abstract: The program is raising awareness about the common cancers and harms of tobacco among the disadvantaged women population in Mumbai. It is also helping in detecting pre-cancers and cancers among asymptomatic women and is assisting them in receiving treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 2 publications
3
8
0
Order By: Relevance
“…In other studies as well like Mishra et al in 2015 and Gangane et al in 2015, they saw that the most of the females belonged to Hindu category i.e. 82.98% and 78.5% respectively [6,9]. This is in accordance with our study.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In other studies as well like Mishra et al in 2015 and Gangane et al in 2015, they saw that the most of the females belonged to Hindu category i.e. 82.98% and 78.5% respectively [6,9]. This is in accordance with our study.…”
Section: Discussionsupporting
confidence: 93%
“…48.2% and 83.2% females in the village belonged to OBC category. This are similar to the findings of the study by Mishra et al [6] probably because of the population based approach used by them as well. Aich et al [7] in their study found that the chances of developing breast cancer were more in elderly age group, the most common being 41-50years and is less in less than 30years age group which is in favour with our study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…IEC and screening are the two main components in cancer prevention recommended by the World Health Organization (Bora et al, 2016). The interim results of a community-based cancer screening conducted in Mumbai showed a compliance rate of 85% and 70% for breast and cervical cancer screening where the women were sensitized about the reproductive organs, cancer symptoms and early detection (Mishra et al, 2015). IEC method and targeted intervention programs have been effective to improve participation in breast and cervical cancer screenings (Jacob, 2012;Rao et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…However, cancer screening in India adopts a camp-based approach. Majority of such screening programs focus on either oral or breast cancer or cervix/ uteri or a combination thereof and largely restricted to urban or semiurban geographies [9][10][11]. None of the existing community-based screening programs provides screening of the oral, breast and cervix/uteri cancers at a single service point for rural communities.…”
Section: Introductionmentioning
confidence: 99%